Behavioral Support Intervention for Uncontrolled Hypertension: A Complier Average Causal Effect (CACE) Analysis. Issue 2 (February 2015) - Liang, Yuanyuan; Ehler, Benjamin R.; Hollenbeak, Christopher S.; Turner, Barbara J.
Abstract : Background: The complier average causal effect (CACE) analysis addresses noncompliance with intervention and missing end-point measures in randomized controlled trials. Objectives: To conduct a CACE analysis for the Peer Coach and Office Staff Support Trial examining the intervention's effect among "compliers, " defined as subjects who would have received an effective dose of the intervention had it been offered, and to compare with an intention-to-treat analysis. Research Design and Subjects: A randomized controlled trial of 280 African American patients aged 40–75 with sustained uncontrolled hypertension from 2 general internal medicine practices. Measures: Change in 4-year coronary heart disease (CHD) risk (primary) and in systolic blood pressure (SBP) (secondary) from the baseline to the end of the 6-month intervention. Results: Of 136 intervention subjects, 68% were compliers who had significantly more end points measured (86% vs. 34% for CHD risk; 99% vs. 57% for SBP) and lower baseline CHD risk (5% vs. 7.5%) and SBP (139 vs. 144 mm Hg) compared with noncompliers. In the intention-to-treat analysis, the effect of offering the intervention was nonsignificant for 4-year CHD risk ( P =0.08) but significant for SBP ( P =0.003). CACE analyses showed that receipt of an effective dose of the intervention resulted in a 1% greater reduction in 4-year CHD risk ( P <0.05) and at least 8.1 mm Hg greater reduction in SBP compared with compliers in the control group ( P <0.05). Conclusions: Among compliers, an effective dose of peer coach and office-based support resulted in significant reductions in 4-year CHD risk and SBP. More intensive interventions are likely to be required for noncompliers.